The precision of FEM simulation results compared with theoretical composite layup calculation. (15th June 2016) - Tafaghodi Helali, Hosein; Grafinger, Manfred
Abstract: Nowadays usage of the composite materials is increasing in many fields of industry. Composite materials have better mechanical properties and heat resistance but lower weight than other materials. Analyzing the composite material in case of using it in mechanical design is inevitable. The FEM analysis is an applicable alternative for theoretical methods and it could be applied for complicated components. As the theoretical calculations for composite components are even more complicated than other materials and sometimes impossible, the comparison between the theory and FEM gives us a useful and trustable replacement for applying the FEM analysis instead of theoretical calculation. The challenge in this paper is to find an appropriate simulation for the composite component based on its load cases; the samples are a cylindrical tube under tension load, and a surface under bending moment. First step is the theoretical calculation based on the ABD matrix formulation. Second approach is the FEM modeling of the components (cylinder, surface), three types of FEM composite modeling with two FEM software (CATIA, ANSYS) are accomplished for these samples. The theoretical calculation is considered as the principal method and three FEM simulations results are compared to the principle result. The output of the first sample are strains and the second are curvatures, comparing the outputs of all methods for each sample creates an overview over the precision and applicability of each FEM method.